PENGARUH KAPASITAS INDIVIDU, KOMITMEN ORGANISASI, DAN LOCUS OF CONTROL TERHADAP BUDGETARY SLACK - Dwi Kriswantini; Annisa Ode (Soso-Q : Jurnal Manajemen, 2017)
This study discusses the effect of individual capacity, organizational commitment and locus of control on budgetary slack to provide evidence of whether individual, organizational commitment and locus of control affect the budgetary slack. This study is a type of survey research by distributing questionnaires to financial managers and finance staff to financial managers and financial staff to State-Owned Enterprises and Regional Owned Enterprises in Ambon City. Questionnaires were distributed to 80 respondents questionnaires.The results of this study provide evidence that individual capacity has no effect on budgetary slack and is not significant, organizational commitment has an effect on budgetary slack and locus of control has no effect on budgetary slack but significant.Keywords: Individual Capacity, organizational commitment, locus of control and budgetary slack.